Validating the Climate Risk Management in Agricultural Extension (CRMAE) Curricula for Livestock Systems - Dinh, Dannie; Hansen, James; Grossi, Amanda (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
The Climate Risk Management in Agricultural Extension (CRMAE) curriculum culminated from collaborative efforts from more than 70 public and private institutions that generate, tailor, communicate, and build capacity to use climate information at the grassroots level. The CRMAE curriculum has since been institutionalized and mainstreamed in various contexts to support agricultural producers. Driven by partner demand in target countries to adapt the CRMAE curriculum for livestock systems in 2025, the AICCRA project and the Jameel Observatory—through its newly launched Drylands Futures Academy—consulted livestock experts, researchers, universities, and grassroots and development organizations targeting pastoralists from Ethiopia, Kenya, and Senegal to catalyze sharing of knowledge, tools, approaches, and innovations amongst the three countries. This report summarizes the consultation process to validate and adapt the CRMAE curriculum for livestock systems in Kenya.